AN EVALUATION OF THE EFFECTIVENESS OF THE PROVISION OF LAND USE POLICY FOR BUILDING HOUSES IN RURAL BANGLADESH (Journal of Governance and Development (JGD), 2024)
The paper provides a comprehensive evaluation of the national land use policy in Bangladesh, highlighting the gaps in implementation and the need for strategic improvements for building houses using minimum agricultural land in rural areas of Bangladesh. The main objectives of the policy evaluation research are to explore the extent of the intervention of the National Land Use Policy 2001 that has achieved the objective of minimum use of agricultural land, to determine whether the authority has made the rural people aware of building model houses, multistorey buildings, and planned residential areas in the village and finally to find out the critical factors for effective implementation of national land use policy. It has been used as a mixed evaluation research method with both qualitative and quantitative approaches. Data were collected online using a semistructured questionnaire and checklist for respondent interviews. The main results of the policy evaluation revealed that the objectives of the policy are not achieved and effectively implemented for numerous reasons as such, the implementers are reluctant to implement and make aware the villagers, responsible implementing agencies are not fully well-defined, people are unaware and do not know about the policy, lack of village development planning and design, overpopulation and segregation of families, poverty, lack of monitoring by the ministry, unorganized urbanization and industrialization, local political influence, absence of land zoning and union parishad are unwilling to enforce their laws, etc. To implement the policy effectively, a joint effort of the local government bodies, local communities, and all local administration departments would be required, and each organization’s role would be well classified, and payment or loan support would be transferred to the rural people of Bangladesh.